INVESTIGATION OF VITAMIN A AND 25(OH)D3 LEVELS IN CATTLE WITH PNEUMONIA DETECTED MYCOPLASMA BOVIS - Dincer, Pelin Fatos Polat; Yerlikaya, Zeynep; Karagulle, Burcu (Sciendo, 2023)
This study investigated the presence of Mycoplasma bovis in nasal swabs taken from cattle with pneumonia, to reveal the clinical and biochemical findings of positive animals, and determine the levels of vitamin A and 25(OH)D-3. In the study were included 103 infected cattle and 10 healthy cattle, all aged 1-4 years, as the control group. Quantitative clinical evaluations and clinical examinations were performed on each animal, and 5 ml blood samples and nasal swabs were taken. Serum biochemistry, vitamin A and 25(OH)D-3 levels were determined in both positive and control samples. The clinical signs were identified by qualitative scoring in M. bovis positive animals. Regarding the clinical findings, respiratory frequency, heart rate, and rectal temperature were significantly higher in positive than control group animals (p < 0.001). Regarding the biochemistry findings, albumin (ALB) and glucose (GLU) levels were lower in cattle infected with M. bovis (p < 0.001) whereas total protein (TP) and alkaline phosphatase (ALP) levels were higher (p < 0.001). While serum 25(OH)D-3 levels were lower in infected animals (p < 0.001), there was no significant difference (p > 0.05) in serum vitamin A levels. In this study, clinical findings in cattle naturally infected with M. bovis were expressed qualitatively and quantitatively. In addition, it has been revealed that the disease does not only cause lung involvement, but also causes changes in biochemical and vitamin levels. Although these parameters cannot be used as a biomarker in the diagnosis of pneumonia, they are thought to provide benefits in terms of diagnosis, treatment and prophylaxis in practice.
Keywords: infectious diseases; internal medicine; Mycoplasma bovis; respiratory system; vitamin D deficiency